Taxonomy of the southernmost populations of Philander (Didelphimorphia, Didelphidae), with implications for the systematics of the genus - Chemisquy, M. Amelia; Flores, David A. (Zootaxa, 2012)
The taxonomic identities of populations of Philander Brisson of Argentina are still unclear. Philander frenatus (Olfers) isthe only species assigned to the country, a conclusion based on incomplete analysis of available material and without aclear taxonomic criterion. The aim of this study was to determine the taxonomic identity of the populations of Philanderof Argentina. To accomplish this, DNA from eight specimens from Argentina and one specimen from Paraguay wassequenced and compared with sequences published by other authors, using a phylogenetic approach. To complement themolecular information, seven skull measurements were taken from specimens of P. frenatus and P. opossum canus(Osgood) from Bolivia and Brazil, and compared with the specimens from Argentina and Paraguay using biandmultivariate analyses. Molecular and morphological results showed that there are two species of Philander in Argentina,P. frenatus in Misiones province and P. opossum canus in Chaco and Formosa provinces. Both species can bemorphologically distinguished only by the width of the postorbital constriction. Finally, the phylogenetic analyses and thepairwise genetic distances between the included sequences showed that the taxonomic status of Philander mcilhennyi, P. opossum and its subspecies should be revisited.